Penguatan Pendididikan Karakter dengan Menggunakan Metode Imtaq dalam Meningkatkan Kualitas Pendidikan di Sekolah Dasar/MI - Suparlan, Suparlan (MASALIQ, 2021)
Character etymologically comes from the Latin character, which means to make sharp. According to the Big Indonesian Dictionary (2008) character is character, psychological traits, morals or character that distinguishes one person from another. Character can also be interpreted as a habit or habit. In general, character is associated with a distinctive or special trait, or a person's pattern of behavior that distinguishes him from others. Imtaq is the formation of two words, namely, faith and taqwa. Faith comes from the word yu'minu-fahuwa mu'min. According to scholars, the meaning of al-iman means "at-tashdiq" or justifies. Al-iman according to shari'ah means to justify by heart everything that was brought by the Prophet Muhammad. Iman means to believe. Believing means that we believe with all our heart that Allah SWT is the only God worthy of worship. While Taqwa comes from the word waqaa-yaqii-wiqaayatan-waqan, which means to maintain and guard. The word taqwa comes from the word ittaqa, thus taqwa is self-preservation and care. Allah SWT with full awareness and devotion, both to His commands and to His prohibitions.